An improved procedure for the preparation of X-ray diffraction-quality crystals of cytochrome p450cam. - Nickerson, D; Wong, L; Rao, Z (1998)
A procedure for the crystallization of recombinant cytochrome P450cam has been developed which avoids the difficulties inherent in the glass-capillary free-interface diffusion method reported previously. The surface mutation, Cys334-->Ala (C334A), originally designed to prevent dimer formation and thus improve routine handling of the enzyme, facilitates crystallization by the hanging-drop vapour-diffusion technique. Crystals of (C334A)P450cam grow within 48 h and diffract to beyond 1.2 A at 100 K in-house on a Siemens multiwire area detector. Data have been collected from the camphor-bound form to 1.35 A.